Extra Connectivity and Extra Diagnosability of Enhanced Folded Hypercube-like Networks - Yihong Wang; Cheng-Kuan Lin (Mathematics)
In the design of multiprocessor systems, evaluating the reliability of interconnection networks is a critical aspect that significantly impacts system performance and functionality. When quantifying the reliability of these networks, extra connectivity and extra diagnosability serve as fundamental metric parameters, offering valuable insights into the network’s resilience and fault-handling capabilities. In this paper, we investigate the 1-extra connectivity and 1-extra diagnosability of the n-dimensional enhanced folded hypercube-like network. Through analysis, we show that the 1-extra connectivity of this network is <semantics>2n+2</semantics>. Moreover, for <semantics>n>5</semantics>, we determine its 1-extra diagnosability under both the PMC model and the MM<semantics>⁢∗</semantics> model to be <semantics>2n+3</semantics>. These results show that as the dimension n increases, both the 1-extra connectivity and 1-extra diagnosability of the network approach approximately twice the value of traditional diagnosability metrics. This provides quantitative insights into the reliability properties of the enhanced folded hypercube-like network, contributing to a better understanding of its performance in terms of connectivity and fault diagnosis.